2021
DOI: 10.52403/ijrr.20210648
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Milk Obtained from Holstein Friesian Cows during First and Second Lactation

Abstract: In this study milk samples from Holstein Friesian cows were collected and analyzed during the first and second lactation period in a period of six months. The following parameters have been examined: protein content, fat content, lactose, and dry matter in milk. The average values of the content of milk protein, fat, lactose and dry matter in the milk of first lactation were as following: 3,14%, 3,25%, 4,46 %, 11,48% and in the milk of second lactation are: 3,21%, 3,29%, 4,39% and 11,68%.%. Milk from cows in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There was a sharp increase in milk production during the early stage of lactation, which continued until the so-called peak of lactation was reached. In the results, it was possible to observe an increase in milk yield while, at the same time, seeing a decrease in the content of milk components (Table 1) [8,[28][29][30][31]. Heuer et al [32] reported that changes in gross composition of milk were useful risk predictors of energy balance in early lactation, e.g., fat/protein ratio > 1.4 and milk fat > 4.8%.…”
Section: Discussionmentioning
confidence: 99%
“…There was a sharp increase in milk production during the early stage of lactation, which continued until the so-called peak of lactation was reached. In the results, it was possible to observe an increase in milk yield while, at the same time, seeing a decrease in the content of milk components (Table 1) [8,[28][29][30][31]. Heuer et al [32] reported that changes in gross composition of milk were useful risk predictors of energy balance in early lactation, e.g., fat/protein ratio > 1.4 and milk fat > 4.8%.…”
Section: Discussionmentioning
confidence: 99%